First-in-human experience of radiopharmaceutical therapy with [177Lu]Lu-DOTATATE in patients with advanced multiple myeloma - Wendy Delbart; Marie Vercruyssen; Rachele Danieli; Clémentine Marin; Zéna Wimana; Nathalie Meuleman; Patrick Flamen; Erwin Woff; Ioannis Karfis (EJNMMI Reports)
Abstract Radiotheranostics using somatostatin receptor (SSTR)-targeted agents has transformed the management of neuroendocrine tumors, yet its application in other oncological entities remains unexplored. Here, we report the first-in-human use of [177Lu]Lu-DOTATATE in two patients with advanced, triple-class refractory multiple myeloma, selected based on dual imaging with [68Ga]Ga-DOTATATE and [18F]F-FDG PET/CT. Both patients received standard activities of [177Lu]Lu-DOTATATE, resulting in favourable safety profiles and improved quality of life. One patient achieved sustained metabolic response and clinical stability over 12 months, while the second showed a complete metabolic response before experiencing biological progression. Treatment was associated with transient, non-clinically significant myelotoxicity. These findings support the feasibility of Peptide Receptor Radionuclide Therapy (PRRT) in multiple myeloma and suggest potential therapeutic benefit in selected patients. Further clinical investigation is warranted to validate these promising preliminary results.